Rancang Bangun Sistem Informasi Rent Car Dengan Pengunaan Aplikasi Online - Ari Abdilah; Badariatul Lailiah; Rabiatus Sa’adah (LPPM Universitas Bina Sarana Informatika, 2021)
PT. Rent Car is one of the companies engaged in the rental car (rent a car). In the process of recording data, officials are still doing by entering the data into the general ledger, so it is considered less effective also make it difficult for the officer to make a report. When a customer wants to rent a car they want, they often feel disappointed because the car is limited and does not know the information about the car that wants to hire. The method used in this research includes methods of data collection and system development methods. Therefore, PT. Rent Car need a rental application system that can integrate the conventional rental system toward online rental system. And specification of software used to design a web-based information system that is using the programming language PHP scripts and to use MySQL database.